A new species of the ammonite genus Physodoceras Hyatt (Aspidoceratidae) from the Hybonotum Zone (Lower Tithonian) of Southern Germany, with comments on the phylogeny of the genus - Scherzinger, Armin (2018)
Fil: Maurenstraße 26, 78194 Immendingen-Hattingen, Germany